Harga Diri Muslimah Obesitas yang Mengalami Penelantaran Rumah Tangga - Titi Ratna Garnasih; Fidia Hanan Zahara (Jurnal Psikologi Islam dan Budaya, 2023)
This study aims to examine the self-esteem of obese Muslim women who experience household neglect. The research used qualitative approach with phenomenological design. Data collection used interview and observation techniques. Participants were 2 women aged 26 and 37 years who were recruited through purposive sampling technique. The obese body condition of both subjects was the reason for neglect by their husbands in the form of physical, verbal and economic violence. The results showed that both subjects rated themselves as worthless. Their low self-esteem can be observed in each component, namely: performance-wise, they are helpless because they are not allowed to work but are not provided for; socially, withdrawing from the environment; and physically, lacks self-confidence because of their obesity. Thus, both participants require psychological treatment such as therapy and spiritual approach.